สารบัญ - Chottanapund, Suthat (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2020)
สารบัญ 1. กองบรรณาธิการ i-ii 2. คำนำ วารสารฉบับที่ 2 ปี 2560 Sutdhachit Linananda คำนำ 3. พลังของ Social Media Pol. Maj. Gen. Chumsak Pruksapong 1-2 4. Evaluation of Alvarado score for diagnosis of appendicitis การประเมินผลของการใช้ระบบคะแนน Alvarado score ในการวินิจฉัยโรคไส้ติ่งอักเสบ Nedtra nedphokaew 3-16 5. Setting a New Endoscopic Retrograde Cholangiopancreatography Team: A Challenge in Establishing a Competent Team and Early Outcomes of ERCP in Sakon Nakhon Hospital Nisit Tongsiri, Witchuda Kittiwararit 17-34 6. Pattern of Initial Permanent Vascular Access in New Hemodialysis Patients in Songklanagarind hospital Suttatip Saemu 35-48